Onde-Onde King - Ag Abdullah, Dg Nurhanani; Madius, Shane Flexwin; G. John, Joyner Joycelin; Jerry, Cynthia Yvonne (2011)
The name of our partnership is DG NURHANANI & PARTNERS. Our business is basically to produce Traditional dessert which is known to Asian as Onde-Onde or Puteri Mandi. It differs from regular Onde-Onde in term of its ingredient as well as the taste. As a start, we will introduce 8 flavors of Onde-Onde. Apart from Onde-Onde, we are also going to sell 10 flavors of beverages. This is to attract more customers as they tend to eat as well as drinks beverages at the same times. Our target customers people of all range of age. Because our product are affordable as well as it is yummy and easy to eat. Moreover, we produce our Onde-Onde with the highest quality and the finest ingredients that can satisfy our potential customer's "wants and preferences". Our business is operating at 1 Borneo Hyper mall Sabah. As for the start, we rent a kiosk that located at the lowest ground of 1 Borneo Hyper mall nearby fast foods outlets such as McDonald as well as Giant. We choose this place as our business operation because it is advantageous in every aspect. In fact, 1 Borneo is the largest Mall in West Asia. Onde-Onde King is expected to commence on 1st July 2013. We believe our business is going to expand in the second year of operation, whereas the sales will increase by 10% the second year and 15% for the third year.